Anti-obesity potential of Moringa olifera seed extract and lycopene on high fat diet induced obesity in male Sprauge Dawely rats - Kilany, Omnia E. (Saudi J Biol Sci, 2020)
Present research explored the anti-obesity effect of Moringa olifera seed oil extract and lycopene (LYC). Forty eight male Sprauge Dawely rats were divided equally into 6 groups. Group Ι (C) served as control, group ΙΙ (MC) was given Moringa olifera seed oil extract (800 mg/kg b.wt) for 8 weeks, group ΙΙΙ (LC) was given (20 mg/kg b.wt) LYC for 8 weeks, group ΙV (O) received high fat diet (HFD) for 20 weeks, group Ѵ (MO), was given HFD for 20 weeks and received (800 mg/kg b.wt) Moringa olifera seed oil extract for last 8 weeks and group ѴΙ (LO), received HFD for 20 weeks and was given (20 mg/kg b.wt) LYC for last 8 weeks. Hematology, lipid peroxidation and antioxidants, non-esterified fatty acids (NEFA), glucose, lipid profile, serum liver and kidney biomarkers, inflammatory markers, leptin, resistin and heart fatty acid binding protein (HFABP) were determined. Also histopathology for liver, kidney and aorta were performed besides immunohistochemistry (IHC) for aortic inducible nitric oxide synthase (iNOS). Administration of Moringa olifera seed oil extract and LYC significantly ameliorated the HFD induced hematological and metabolic perturbations as well as reduced leptin and resistin. Both treatments exerted these effects through promotion of antioxidant enzymes and reducing lipid peroxidation as well as inflammatory cytokines along with reduced iNOS protein expression. Administration of Moringa olifera seed oil extract and LYC have anti-obesity potential in HFD induced obesity in male Sprauge Dawely rats.